Two Different Worlds: Television as a Producer’s Medium - Coleman, Robin R. Means; Cavalcante, Andre M. (Watching While Black, 2012)
Although discourses regarding 1980s representations of Blackness on television heavily focus on The Cosby Show, its NBC spin-off series, A Different World, depicting student life at a historically Black college, was equally groundbreaking and deserving of critical attention. Looking to transfer the appeal and audience share of The Cosby Show to A Different World, the spin-off show’s first season centered on the life of The Cosby Show’s star Denise Huxtable (Lisa Bonet) at Hillman College. A Different World’s story provides an illuminating case study of the role and power of television producers, highlighting their influence over a show’s narrative and
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé; États-Unis (corpus analysé)

Introduction: I See Black People - Smith-Shomade, Beretta E. (Watching While Black, 2012)
This project has been engaging my thoughts for nearly a decade. I was forced to actually address it while sitting in our temporary home in Ile-Ife, Nigeria, watching world satellite TV with virtually no Blacks on it. In Nigeria, I became acquainted with Paris-based Fashion TV, U.S.-based Style Network, and the Australian production McLeod’s Daughters. Outside of M-Net’s Africa Magic, a network dedicated to showing Nollywood productions primarily, television was anything but Black. This whitening of the televisual frame, even in Black Africa, made me begin to consider the dearth of knowledge circulating about Black television programming, even when abundance
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice noir.e; 5-Créateur.rice PANDC; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Neoliberal Multiculturalism, Outsourced - Nadkarni, Asha (The Routledge Companion to Global Television, 2019)
This essay examines the 2010 NBC situation comedy Outsourced, with special attention to its representation of the racial politics surrounding business process outsourcing to India. Specifically, it discusses how Outsourced participates in what Jodi Melamed calls “neoliberal multiculturalism” to work through, symbolically and narratively, the realities and contradictions of globalized economies as they are experienced. By staging the dilemmas of outsourcing through the specter of the white male middle manager traveling to India to train Indian call center workers, Outsourced minimizes the affective labor necessarily performed by Indian call center workers and dramatizes outsourcing as a crisis of white U.S. masculinity alone. Moreover, it figures our white male protagonist as the global multicultural citizen to be emulated insofar as he models the appropriate attitude toward outsourcing and toward “other” cultures in general. Finally it suggests that the failure of the show has less to do with issues of cultural stereotyping and more to do with the failure of neoliberal multiculturalism to soothe anxieties around changing global economies.
Keywords: 1-TV; 2-Approches sociologiques; 2-Méthodologie de recherche décoloniale; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice PANDC; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)